2015
DOI: 10.1038/srep07663
|View full text |Cite
|
Sign up to set email alerts
|

Three CCT domain-containing genes were identified to regulate heading date by candidate gene-based association mapping and transformation in rice

Abstract: CCT domain-containing genes generally control flowering in plants. Currently, only six of the 41 CCT family genes have been confirmed to control flowering in rice. To efficiently identify more heading date-related genes from the CCT family, we compared the positions of heading date QTLs and CCT genes and found that 25 CCT family genes were located in the QTL regions. Association mapping showed that a total of 19 CCT family genes were associated with the heading date. Five of the seven associated genes within Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 61 publications
7
61
0
Order By: Relevance
“…Furthermore, Hd1 and OsCCT1 were reported to have a CCT domain to regulate heading date and panicle size (Endo‐Higashi and Izawa , Zhang et al. ) and were associated with rachis length in this study as well. These genes were not detected by the GWAS for panicle length, as was reported by Zhao et al.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Furthermore, Hd1 and OsCCT1 were reported to have a CCT domain to regulate heading date and panicle size (Endo‐Higashi and Izawa , Zhang et al. ) and were associated with rachis length in this study as well. These genes were not detected by the GWAS for panicle length, as was reported by Zhao et al.…”
Section: Discussionsupporting
confidence: 63%
“…The overexpression of OsCCT1 and wild‐type Zhonghua 11 plants was reported in a previous study (Zhang et al. ).…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…Previous studies have indicated that most COL genes exhibit diverse roles, including flowering, circadian rhythm and root growth, in plant development [54,55]. Therefore, it is necessary to determine the precise function of OsCOL9 during plant development in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several heading date-related genes have been identified and isolated throughout 12 chromosomes by some researchers . Hori et al, 2015;Lee and An 2015;Zhang et al, 2015;Zhan et al, 2015). Study on the structure of genes associated with response to photoperiod on flowering of rice has been reported by Nakamichi 2015 andYoshitake et al, 2015, which is triggered by day length (Ichitani et al, 2014) and is regulated by many genes (Itoh and Izawa 2013;Tsuji et al 2011), andEbana et al (2011) also reported as a negative control.…”
Section: Introductionmentioning
confidence: 99%